PENGARUH PROFIL MANAJER TERHADAP PRAKTEK CSR MELALUI PERCEIVED ROLE OF ETHICS AND SOSIAL RESPONSIBILITY SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR KOTA SEMARANG - Ronia Tambunan (Jurnal Akuntansi Bisnis, 2017)
Abstract In Indonesia, the Law on Social and Environmental Responsibility (known as CSR) has been enforced. CSR has been contained in Law No.40 of 2007 on Limited Liability Company Article 74 on Social and Environmental Responsibility. In CSR practice, an important role of manager in the implementation of corporate CSR practices is required. Social responsibility is always accompanied by the social responsibility of managers who are sometimes willing to sacrifice company goals, interests and company needs to support social responsibility actions. Manager profiles show sympathetic to ethics and social responsibility and integrate them through management strategies (Jose'-Luis et al., (2010). The manager profile distinguishes between agency and stewardship models. The agency model shows individuals tend to behave opportunistically and the main concern is improving their own well-being as well as maximizing shareholder value. Meanwhile, the stewardship model tends to behave collectively with the interests of the organization and all stakeholders. The influence of manager profiles on CSR practices is mediated by perceived role of ethics and social responsibility. The measurement of the management profile variable using the 5-point Likert scale is cited from Jose'-Luis et al. (2010), the perceived role of ethics and social responsibility using the model developed by Singhapakdi et al., (1996), while the CSR practice variables use GRI guidelines . This research was conducted at manufacturing company of Semarang City. Respondents who are the samples of this research are managers in manufacturing companies with BPS data 2014. This study collected 47 managers participated in the survey by answering the questionnaire given. The results of this study indicate that the Manager Profile has no effect on CSR Practices through Perceived Role Of Ethics and Social Responsibility. This is because companies do not good CSR practices and not continuously based on GRI content guidelines. This indicates that the manager profile of both stewardship and agency approach has no effect on CSR Practices through perceived role of ethics and social responsibility.